Growth and yield of maize in response to reduced fertilizer application and its impacts on population dynamics and community biodiversity of insects and soil microbes - Yan Zou; Likun Li; Yanhui Wang; Ruichuan Duan; Hejie Dong; Yuhan Zhang; Zhengze Du; Fajun Chen (Frontiers in Plant Science, 2024)
In the North China Plain, farmers are using excessive amounts of fertilizer for the production of high-yield crop yield, which indirectly causes pollution in agricultural production. To investigate an optimal rate of fertilizer application for summer maize, the fertilizer reduction experiments with 600 kg/ha NPK (N: P2O5: K2O = 28: 8: 10) as normal fertilizer application (NFA), (i.e., 100F), were conducted successively during 2020 and 2021 to study the effects of reduced fertilizer rates, including 90% (540 kg/ha; i.e., 90F), 80% (480 kg/ha; i.e., 80F), 62.5% (375 kg/ha; i.e., 62.5F) and 50% (300 kg/ha; i.e., 50F) of NFA, on the plant growth of maize, the dynamics of key population abundances and community diversity of insects, and the composition and diversity of microbial community and finally to find out the N-metabolic enzymes’ activity in soil. Our findings revealed that the fertilizer reduction rates by 10% - 20% compared to the current 100% NFA, and it has not significantly affected the plant growth of maize, not only plant growth indexes but also foliar contents of nutrients, secondary metabolites, and N-metabolic enzymes’ activity. Further, there was no significant alteration of the key population dynamics of the Asian corn borer (Ostrinia furnacalis) and the community diversity of insects on maize plants. It is interesting to note that the level of N-metabolic enzymes’ activity and microbial community diversity in soil were also not affected. While the fertilizer reduction rate by 50% unequivocally reduced field corn yield compared to 100% NFA, significantly decreased the yield by 17.10%. The optimal fertilizer application was calculated as 547 kg/ha (i.e., 91.17% NFA) based on the simulation analysis of maize yields among the five fertilizer application treatments, and the fertilizer application reduced down to 486 kg/ha (i.e., 81.00% NFA) with a significant reduction of maize yield. These results indicated that reduced the fertilizer application by 8.83% - 19.00% is safe and feasible to mitigate pollution and promote sustainable production of maize crops in the region.